Ontologia relazionale ricerche sulla filosofia classica tedesca - Marco Ivaldo (Scuola delle Scienze Umane e Sociali. Quaderni, 2019)
The volume contains the proceedings of the conference on the subject of relational ontology, which involved a group of scholars of classical German philosophy with the aim of explaining the reasons, drawing inspiration and categories from the ideal and conceptual constellation of that age of culture. The idea from which they make the contributions is that for relational ontology we can understand a theory on the structure of reality (onto-logic), attentive to the development of the explanatory and normative potential of the category of reciprocity. The contributions thus define a path that, starting from Kant and the question of a unity and duplicity of the ego, passing through the consideration of the Fichtian relational ontology and the idea of a constitution of identity responding to the appeal from the other (on this theme a dialogue Ricoeur / Fichte is also staged), it touches on the notion of natural law of Schelling, to arrive at the Hegelian construction of an ontology and logic of the relationship, which can be found in the very notion of civil society, and finally to reading in a 'materialistic' key of Kantian transcendental idealism, in relation to the notion of reciprocal action.